The girl who was taken - Donlea, Charlie (New York : Kensington Books, 2017)
Nicole Cutty and Megan McDonald are both high school seniors in the small town of Emerson Bay, North Carolina. When they disappear from a beach party one warm summer night, police launch a massive search. No clues are found, and hope is almost lost until Megan miraculously surfaces after escaping from a bunker deep in the woods.
Nicole Cutty and Megan McDonald are both high school seniors in the small town of Emerson Bay, North Carolina. When they disappear from a beach party one warm summer night, police launch a massive search. No clues are found, and hope is almost lost until Megan miraculously surfaces after escaping from a bunker deep in the woods. Years later, Megan is a celebrity; Nicole is still missing. Nicole's sister Livia, a forensic pathologist, begins to find clues to her sister's disappearance and reaches out to Megan. But Megan knows more than she revealed in her book....
Keywords: Young women -- Fiction; Murder -- Investigation -- Fiction; Forensic pathologists -- Fiction; High school students -- Crimes against -- Fiction; Missing persons -- Fiction; FICTION / Crime; FICTION / Thrillers / Psychological; FICTION / Thrillers / Suspense; Missing persons -- Fiction; North Carolina -- Fiction; Suspense fiction; North Carolina -- Fiction; Suspense fiction; Thrillers (Fiction)